Urgensi Komunitas Hijrah di Kota Tasikmalaya sebagai Kota Santri: Studi Komunitas Siram Tasik - Sholehah, Adhe Noer; Listy Tilania; Zidan Ramadan Muhammad Darda; Muhamad Parhan (MADINAH, 2023)
Hijrah is defined as a process of changing a person’s attitude, behavior and lifestyle in a better direction because they have an awareness of their religion which is increasing or more religious, especially for Muslims. At this time, hijrah has become a popular movement among the younger generation of Indonesia which is marked by the many hijrah communities that have sprung up in various cities, such as the Siram Tasik community (Mosque Youth Symphony) which is one of the communities engaged in religious activities in the City of Tasikmalaya. Apart of conducting regular studies, the Siram Tasik community also presents mentors to provide specific materials that are problematic among the younger generation. Therefore, the author is interested in researching the phenomenon of hijrah in Tasikmalaya City known as the City of Santri through the Siram Tasik community to find out the initial purpose of creating this community and how big the positive impact is for society, especially teenagers in Tasikmalaya City. This research was conducted using the interview method with several members of Siram Tasik and participant who actively participated in activities held by this community Keywords: Hijrah; Muslim; Milennials; Community